Determination of Anemia Iron Deficiency Anemia and β-thalassemia during Pregnancy - Shazia Batool, Syeda Tahira Sherazi, Amna Noor, Tayyaba Wasim, Sana Javed, Ayesha Hussain Sial, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To observe the frequency of anemia, iron deficiency anemia and β-thalassemia during pregnancy. Study type, setting & duration: This cross sectional study was undertaken at antenatal clinic of gynecology, Unit V of Lady Aitcheson Hospital Lahore from October 2018 to March 2019. Methodology: The study was commenced after formal written permission. A total of 310 pregnant women were included in this study andtheir demographic information was taken on predesigned Performa. Blood samples from all females were collected from the peripheral vein of upper limb and was sent to hospital laboratory for analysis of Hemoglobin and other necessary parameters. All female were labeled as iron deficiency anemia or β thalassaemia as per operational definition. Data was entered and analyzed in SPSS. Results: Mean age of females was 26.23± 5.26 years and mean gestational age was remained to be 16.632±10.62 weeks. The mean hemoglobin 8.55±2.10 g/dl, mean iron binding capacity was 13.07 ± 6.55 µg/dl and mean serum ferritin was 43.50 ± 76.93 µg/L. Anemia was seen in 270(87.1%), iron deficiency anemia was diagnosed in 239(77.1%) while β thalassemia was seen in 29(9.4%) of the pregnant women. There was significant association between parity with anemia and β thalassemia, p-value < 0.05. While iron deficiency anemia was not associated with parity. Conclusion: Anemia, iron deficiency anemia and β-thalassemia are much high and require recognition at early gestations. Various factors are reported to be involved which may be controlled by early supplementation. Keywords: Anemia, Iron deficiency, β-thalassemia, pregnancy, trimester, parity.